"Somos ya legión": Mapping Modernista Poetics and Literary Production. Issue 3 (23rd June 2017) - Reynolds, Andrew
This study investigates how digital mapping of lyrical spaces and publication statistics illuminate modernista participation of the global literary field. Using gathered spatial data points from poetic editions from Rubén Darío and Amado Nervo reveal a rich intertextual and geospatial web. The cosmopolitanism and globalized erudition of modernista writers granted them wide access to seize world cultures and created a hybridized conglomeration of spatial elements in their poetic expression. The article then shifts to the mapping of literary production of Darío and Enrique Gómez Carrillo. Through data collection and geographic mapping of the writers' book and journalistic publishing, levels of transnationality come into focus revealing previously unseen patterns of print and communication technologies at the turn of the 20 th century. Tools of data collection and mapping prompt a greater understanding of the narrative of the modernista movement. Instead of leading to unambiguous and objective results, mapping spatial elements of the period lead to further questions that have the potential to open up the literary history of the fin de siglo to lines of inquiry that are not yet fully explored.